Annexin 2 & P11-Expression, Purification and Biophysical Characterization - Kaur, Kritika (My University, 2015)
Annexin 2 fits in with the class of proteins that tie to acidic phospholipids in a calcium subordinate way which has prompted the proposal that it capacities in exocytosis, endocytosis and cell-cell adhesion. This makes this protein an interesting molecule to study in detail. With a specific end goal to portray the interactome of annexin II , we have over expressed, purified & characterized annexin II & one of its communicating partner S100A10 (P11). We have additionally affirmed the association between annexin II & S100A10 (P11) by CoImmunoprecipitation test.
Master of Science (Biotechnology)
Keywords: Annexin II; P II; CD; UV spectra; Fluorescence; DBT